The Effect of Collage Games on Fine Motor Skills and Creativity in Early Childhood - Nurdin (Jurnal Pendidikan Anak Usia Dini Undiksha, 2026)
Limited learning stimulation that can optimally develop fine motor skills and creativity in early childhood remains a challenge in the educational process. This highlights the need to implement more innovative, varied, and developmentally appropriate learning strategies to support the optimization of these two aspects. This study aims to analyze the effect of collage games on early childhood fine motor skills and creativity, both partially and simultaneously. This research used an experimental method with a design to examine differences in the effects of the treatment applied. The subjects of the study were 25 children. Data collection was carried out through documentation and performance tests used to measure fine motor skills and creativity through pre-test and post-test. The research instruments consisted of observation sheets and assessment rubrics. Data analysis was conducted using an independent sample t-test and Multivariate Analysis of Variance (MANOVA). The results showed that collage games had an effect on children’s fine motor skills, an effect on early childhood creativity, and a simultaneous effect on both variables. These findings indicate that collage games are effective in improving early childhood fine motor skills and creativity. The implication of this study is that collage games can be utilized as an innovative learning strategy in early childhood education to optimize the integrated development of fine motor skills and creativity.